If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(c + 10) = -88 Reorder the terms: -8(10 + c) = -88 (10 * -8 + c * -8) = -88 (-80 + -8c) = -88 Solving -80 + -8c = -88 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '80' to each side of the equation. -80 + 80 + -8c = -88 + 80 Combine like terms: -80 + 80 = 0 0 + -8c = -88 + 80 -8c = -88 + 80 Combine like terms: -88 + 80 = -8 -8c = -8 Divide each side by '-8'. c = 1 Simplifying c = 1
| -5=c*7 | | 6-2= | | 61-2x=7x+17 | | 8-5r+16=-21 | | 4x^2-12x=-4x^2-3x-1 | | x/3-2=6 | | -5x=+x-1 | | 3x+9=6(x-2) | | -54-10x=10x+16 | | 2(-3)-5y=13 | | 9k+ar=r-2y | | 32=-4(3p+7) | | -1=-5x | | 2(-3)5y=13 | | 3-(2x-5)=7 | | 2(5m-6)=28 | | p-3q=10 | | 3(2a+1)-4=11 | | 9v^2=-30v-25 | | 6x-5x=+1 | | 6w-14-9w=-5 | | 5-3*-1= | | 12y-3y+7=88 | | 8x^2+3x-7=0 | | 22p+11= | | 8(y+3)=2(2y+4) | | 4w^2+5=-21w | | 2(3)-5y=13 | | 7y=20 | | 3(x-2)+4x=8 | | 3x-10-5+6x=12 | | 4(7x-2)-16x= |